No easy harvest : the dillemma of agricultture in underdeveloped countries - Millikan, Max F. (Massachusetts : Massachusetts Institute of Technocolgy, 1967)
This publication examines agricultural productivity as it relates to food production in underdeveloped nations.
Includes Index
lje 16/06/17
Loans
Keywords: Agriculture; Agriculture--Economic aspects; Developing countries